2009
DOI: 10.1002/rcm.4328
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics profiling of extracellular metabolites in recombinant Chinese Hamster Ovary fed‐batch culture

Abstract: A metabolomics-based approach was used to time profile extracellular metabolites in duplicate fed-batch bioreactor cultures of recombinant Chinese Hamster Ovary (CHO) cells producing monoclonal IgG antibody. Culture medium was collected and analysed using a high-performance liquid chromatography (HPLC) system in tandem with an LTQ-Orbitrap mass spectrometer. An in-house software was developed to pre-process the LC/MS data in terms of filtering and peak detection. This was followed by principal component analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 22 publications
0
57
0
1
Order By: Relevance
“…An ultraperformance LC Acquity system (Waters Corporation) coupled to a high-resolution mass spectrometer, Xevo Q-TOF (Waters Corporation), was used for intracellular lipid profiling. The LC-MS data preprocessing was described previously (Chong et al, 2009; see the Supplemental Experimental Procedures for details of LC setup parameters). Masses of shortlisted peaks were compared against entries in the Kyoto Encyclopedia of Genes and Genome and the Human Metabolome Database.…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%
“…An ultraperformance LC Acquity system (Waters Corporation) coupled to a high-resolution mass spectrometer, Xevo Q-TOF (Waters Corporation), was used for intracellular lipid profiling. The LC-MS data preprocessing was described previously (Chong et al, 2009; see the Supplemental Experimental Procedures for details of LC setup parameters). Masses of shortlisted peaks were compared against entries in the Kyoto Encyclopedia of Genes and Genome and the Human Metabolome Database.…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Ornithine, an amino acid produced in the urea cycle by splitting of urea from arginine (Wishart et al 2009) has been reported to have apoptotic properties (Tobias and Kahana 1995). Previously, arginine has also been reported to be in excess supply in culture media leading to accumulation of apoptosis induction by dimethylyarginine (Chong et al 2009). In this study, lysine was also found in the death phase, suggesting an over-supply of this essential amino acid.…”
Section: Discussionmentioning
confidence: 96%
“…While these approaches have aided in understanding and improvement of CHO cell culture system, the more recent metabolomics techniques have increasingly being used to investigate other metabolites (beyond the routine measurement of glucose, glutamine and lactate) potential for better understanding of the culture system. For example, a liquid chromatography mass spectrometry (LCMS) based study found that acetylphenylalanine and dimethylarginine accumulate when CHO fed-batch culture entered stationary phase, which corresponds to their detrimental effect to cell growth (Chong et al 2009). Later, the same group reported that aspartate supplied in the medium formulation resulted in malate efflux leading to higher cell density and improved product titer of the culture system in study (Chong et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…However, with the advancements in analytic high-throughput technologies such as liquid chromatography-mass spectrometry based metabolomics, it is possible to profile a multitude of extracellular metabolites as well as various medium components covering cofactors, amino acid derivatives, vitamin, sugar molecules, etc. (Schroer et al, 2009;Shulaev, 2006;Chong et al, 2009). Thus, increased information on medium components and relevant metabolites can be exploited to achieve better understanding of the intricate characteristics of mammalian cell culture through the use of currently available multivariate statistical techniques.…”
Section: Multivariate Statistical Analysismentioning
confidence: 97%